2021
DOI: 10.1055/s-0041-1731788
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Paravertebral Block Ameliorates Postoperative Delirium in Geriatric Patients

Abstract: Objectives Thoracic surgery often causes postoperative delirium (POD) in geriatric patients. This study aimed to explore the effect of ultrasound-guided continuous thoracic paravertebral block (UG-TPVB) on POD in geriatric patients undergoing pulmonary resection. Methods Total 128 patients who underwent pulmonary resection were randomly allocated to either the conventional patient-controlled analgesia (PCA) group or the UG-TPVB group (n = 64 per group). The consumption of opioid agents (propofol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The advantages are that it can provide a more extensive and deeper thoracic nerve block, covering the pain‐sensitive areas of the thorax, reducing drug dosage and adverse reactions; it can also avoid affecting the movement of the diaphragm and cough reflex, reducing the risk of mechanical ventilation time and postoperative pulmonary infection. Previous studies have confirmed the application value of UG‐TPVB in lung cancer radical surgery 12–14 . It can improve the problems existing in traditional anesthesia management of elderly patients, such as excessive and side effects of opioids, respiratory dysfunction, cardiovascular complications, and so on.…”
Section: Introductionmentioning
confidence: 76%
“…The advantages are that it can provide a more extensive and deeper thoracic nerve block, covering the pain‐sensitive areas of the thorax, reducing drug dosage and adverse reactions; it can also avoid affecting the movement of the diaphragm and cough reflex, reducing the risk of mechanical ventilation time and postoperative pulmonary infection. Previous studies have confirmed the application value of UG‐TPVB in lung cancer radical surgery 12–14 . It can improve the problems existing in traditional anesthesia management of elderly patients, such as excessive and side effects of opioids, respiratory dysfunction, cardiovascular complications, and so on.…”
Section: Introductionmentioning
confidence: 76%
“…Five trials not fulfilling the inclusion criteria were excluded after full-text screening (online supplemental table 1). Twenty-six RCTs enrolling 4414 patients with a mean age of 70.69 years were included in this systematic review and meta-analysis 25–50. Of these, 2251 patients were enrolled in the RAB group, and 2163 were assigned to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Six trial authors included patients undergoing emergent/urgent procedures (fractures),27 33 42 43 47 49 whereas the rest included elective surgery patients. Two trial authors evaluated the effect of the combination of two or more blocks,28 41 whereas the rest of the trials used only a single block within the study. Most trial participants received general anesthesia, and neuraxial anesthesia was used as an anesthetic technique in two trials 33 49.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By a randomized controlled trial (RCT) of 128 geriatric patients undergoing pulmonary resection, Heng et al 1 showed that in comparison to conventional patient-controlled analgesia (PCA), continuous thoracic paravertebral block (CTPB) decreased the incidence of postoperative delirium (POD) and improved postoperative pain control. The findings of this study have potential clinical implications, but there are several methodological issues on which we wish to invite the authors to comment.…”
mentioning
confidence: 99%